Exosomal IRF1-loaded rat adipose-derived stem cell sheet contributes to wound healing in the diabetic foot ulcers - Min Wu; Jun Tu; Jinjun Huang; Huicai Wen; Yuanlin Zeng; Yingjie Lu (BMC, 2023)
Abstract Background Cell-based therapy has been recognized as a novel technique for the management of diabetic foot ulcers, and cell-sheet engineering leads to improved efficacy in cell transplantation. This study aims to explore the possible molecular mechanism of the rat adipose-derived stem cell (ASC) sheet loaded with exosomal interferon regulatory factor 1 (IRF1) in foot wound healing. Methods Rats were rendered diabetic with streptozotocin, followed by measurement of miR-16-5p expression in wound tissues. Relationship between IRF1, microRNA (miR)-16-5p, and trans-acting transcription factor 5 (SP5) was analyzed using luciferase activity, RNA pull-down, and chromatin immunoprecipitation assays. IRF1 was overexpressed in rat ASCs (rASCs) or loaded onto the rASC sheet, and then exosomes were extracted from rASCs. Accordingly, we assessed the effects of IRF1-exosome or IRF1-rASC sheet on the proliferation and migration of the fibroblasts along with endothelial cell angiogenesis. Results miR-16-5p was poorly expressed in the wound tissues of diabetic rats. Overexpression of miR-16-5p promoted fibroblast proliferation and migration as well as endothelial cell angiogenesis, thus expediting wound healing. IRF1 was an upstream transcription factor that could bind to the miR-16-5p promoter and increase its expression. In addition, SP5 was a downstream target gene of miR-16-5p. IRF1-exosome from rASCs or the IRF1-rASC sheet facilitated the foot wound healing in diabetic rats through miR-16-5p-dependent inhibition of SP5. Conclusion The present study demonstrates that exosomal IRF1-loaded rASC sheet regulates miR-16-5p/SP5 axis to facilitate wound healing in diabetic rats, which aids in development of stem cell-based therapeutic strategies for diabetic foot wounds.